The Influence of Motivation, Dicipline and Work Environment on Employee Performance CV Nusadaya Sira Indonesia - Didik Setiyadi (Institute of Computer Science (IOCS), 2022)
This study aims to examine and analyze the influence of motivation, discipline and work environment on employee performance at CV. Nusadaya Sira Indonesia. This research was conducted using quantitative methods with descriptive and verification analysis, namely collecting, presenting, analyzing, and testing hypotheses, as well as making conclusions and suggestions. The sample in this study amounted to 108 using the Non Probability Sampling technique with the Saturated Sample method. Based on the analysis that has been done, this study proves that employee motivation at CV. Nusadaya Sira Indonesia is good, employee discipline at CV. Nusadaya Sira Indonesia is quite good, the work environment of employees at CV. Nusadaya Sira Indonesia is good and employee performance at CV. Nusadaya Sira Indonesia is good. The correlation coefficient between the variables of Motivation, Discipline and Work Environment has a strong, positive and significant correlation level. The influence of the work environment variable coefficient contributes to performance more than motivation and discipline. The simultaneous influence of work motivation, discipline and work environment on employee performance is 67.1% while the remaining 32.9% is the contribution of other variables not examined.